Recycling waste practice in campus towards a green campus and promotion of environmental sustainability - Maidiana Othman,; Nordila Ahmad,; Zuliziana Suif,; Jestin Jelani,; Vikneswaran Munikanan,; Md Firdaus Md Farid, (Penerbit Universiti Kebangsaan Malaysia, 2021)
A study has been conducted to determine the amount of recycle waste and the effective method of recycling management at Faculty of Engineering, Universiti Pertahanan Nasional Malaysia (UPNM) using the recycling bins system to reduce waste disposal at landfills. The primary data were collected through daily waste collection in Faculty of Engineering, UPNM. Several recycle waste bins have been located at specific areas to ease student and staff the throw the recycle waste. The result showed that the recycling bin system successfully recovered recycle waste item by 3 000 to 5 000 gram. Thus, it is believing that the implementation of waste separation at source can improve the current waste management system in UPNM and helps to support the sustainability and green campus environment campaign.